Cameroon : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The paper provides an overview of recent economic and social developments in Cameroon. The state and the dynamics of poverty has been analyzed. The pillars of the short- and medium-term growth and poverty reduction strategy have been described. The paper provides a quantitative assessment and costing of Cameroon's poverty reduction strategy, a consistency check between the macroeconomic framework and sector strategies, and estimates of the total cost of the strategy. It also explains how the poverty reduction strategy will be monitored and evaluated.